Brown coal waste in South Kazakhstan: Assessment of physicochemical and biological characteristics - Alikhan, Akmaral Zh.; Tlegenova, Kulaisha; Issayeva, Akmaral. U.; Rakhimberdiyeva, Zhanar; Zhantassova, Dina (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to determine the physico-chemical and biological characteristics of brown coal waste in southern Kazakhstan and to understand the processes occurring within the waste column and surrounding storage areas, particularly as industrial waste storage increasingly encroaches on metropolitan limits due to rapid urbanization. The research employed scanning electron microscopy (SEM) with combined elemental analysis to identify chemical components. Diffractometric analysis was conducted to determine the mineralogical composition of the crystalline part of waste samples. SEM analysis revealed the presence of elements including Na, Mg, Al, Si, S, K, Ca, Ti, and Fe. Diffractometric analysis identified numerous mineral compounds including quartz (SiO₂), gypsum (CaSO₄×2H₂O), kaolinite (Al₂Si₂O₅(OH)₄), cronstedtite (Fe₃((Si₀.₇₄Fe₀.₂₆)₂O₅)(OH)₄), margarite (CaAl₂(Si₂Al₂)O₁₀(OH)₂), muscovite (H₂KAl₃(SiO₄)₃), calcite (CaCO₃), laumontite (CaAl₂Si₄O₁₂(H₂O)₂), and lead aluminum sulfate hydroxide (Pb₀.₅Al₃(SO₄)₂(OH)₆), with varying ratios across samples. The phytocenoses were dominated by ruderal species of local flora, particularly Dodartia orientalis L., Polygonum aviculare L., Elytrigia repens (L.) Nevski, and Centaurea pseudosquarrosa Mikheev ex Gabrieljan et Mikheev. The study established that natural biological transformation of carbon-containing waste components occurs at storage sites, with microorganisms from genera Rhodococcus, Bacillus, Pseudomonas, Penicillium, Trichoderma, and Dietzia playing significant roles in these processes. Natural biological transformation of carbon-containing waste components occurs in brown coal waste storage sites in southern Kazakhstan. These findings can inform the development of bioremediation approaches specifically tailored to brown coal waste sites in Kazakhstan and similar regions.